Indicadores para atuação do psicólogo escolar no processo de inclusão de estudantes autistas durante e após a pandemia pela covid-19 - OLIVEIRA, Mônica dos Santos de (2024)
The number of students diagnosed with Autism Spectrum Disorder (ASD) enrolled in mainstream classrooms has been growing as a result of the expansion of inclusive education policies, especially in the last two decades. In the midst of these policies, the global health crisis caused by COVID-19 has had repercussions for the schooling of these students, which was already being managed with many problems regarding quality access and permanence in mainstream education. It can be seen that the work of the school psychologist to meet this demand needed to be expanded and reframed during and after the pandemic in the face of the contemporary challenges of school inclusion. This research investigated the indicators for school psychology work aimed at monitoring autistic students after the pandemic in a public school in Caxias/MA. Four specific objectives were outlined: (1) to map the number of autistic students enrolled in municipal public schools; (2) to find out the strategies used by schools to teach students with and without disabilities, in relation to sanitary protection measures, during the pandemic context, including the return to face-to-face classes; (3) to verify the demands that emerged or intensified during and after COVID-19 for the school psychologist's work in the inclusion of autistic students; and (4) to identify, based on the routines and activities of a school, indicators for the work of school psychologists aimed at including autistic people. Qualitative in nature, the research was based on the institutional intervention proposal of critical school psychology (Marinho-Araujo, 2014, 2016, 2018) and the cultural-historical perspective of human development (Vygotsky, 2012), which took place in two stages: (1) Mapping of schools with autistic students enrolled in Caxias-MA; and (2) Institutional Intervention. The construction and analysis of the information enabled the development of five guiding axes for discussion, which gave rise to seven zones of meaning: (a) Inclusion practices for autistic students to prevent COVID-19: the exacerbation of ableism in the school environment; (b)Practices implemented for all and lack of specific measures for autistic students; (c) The pandemic as a magnifying glass for the challenging realities of autistic students; (d) Disengagement from schools and the hopelessness of atypical families with the educational process; (e) Giving up on the teaching and learning process for autistic students; (f) Readapting to the school context and the emergence of new challenges; and (g) Reduced understanding of the role of school psychologists. The results indicated a lack of specific actions for teaching self-protection measures for autistic students in and by the collective, as well as training needs in the theoretical and methodological fields for school actors for this purpose. Also noteworthy is the exacerbation of ableism aimed at atypical students during and after the pandemic period, which increased the dropout rate from pedagogical interventions related to school aspects and also for teaching prevention and safety measures against infectious diseases, which minimizes the potential of teacher mediation when directed at this audience. There was a recurrence of statements aimed at a mistaken attribution of the role of the family in the school education of students with and without disabilities during the period of suspension of face-to-face classes, but with a minimization of demands aimed more at atypical families. The information found led to the conclusion that dropping out of the teaching and learning process, the emotional and behavioral impacts of breaking routine during the pandemic and the difficulties of reintegrating into the school context were more pronounced among autistic students. Based on the results and conclusion of the research, guidelines were drawn up for expanding and reframing the work of school psychologists in pandemic scenarios, with a view to strengthening the anti-capacity struggle in tackling the inclusion of autistic people. Based on the results and conclusion of the research, guidelines were drawn up for expanding and reframing the work of school psychologists in pandemic scenarios, with a view to strengthening the anti-capacity struggle in the face of the inclusion of autistic people. It is hoped that the results of this study will help to build democratic, pluralistic schools that naturalize the power of the differences in forms of human existence among the neurodiverse population.